2020
DOI: 10.1097/cm9.0000000000000839
|View full text |Cite
|
Sign up to set email alerts
|

Lung transplantation as therapeutic option in acute respiratory distress syndrome for coronavirus disease 2019-related pulmonary fibrosis

Abstract: Background Critical patients with the coronavirus disease 2019 (COVID-19), even those whose nucleic acid test results had turned negative and those receiving maximal medical support, have been noted to progress to irreversible fatal respiratory failure. Lung transplantation (LT) as the sole therapy for end-stage pulmonary fibrosis related to acute respiratory distress syndrome has been considered as the ultimate rescue therapy for these patients. Methods From February 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
176
1
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 160 publications
(183 citation statements)
references
References 9 publications
2
176
1
4
Order By: Relevance
“…The characteristics of included trials were presented in Table 1 . A total of 269 patients from 47 studies [16] , [17] , [18] , [19] , [20] , [21] , [22] , [23] , [24] , [25] , [26] , [27] , [28] , [29] , [30] , [31] , [32] , [33] , [34] , [35] , [36] , [37] , [38] , [39] , [40] , [41] , [42] , [43] , [44] , [45] , [46] , [47] , [48] , [49] , [50] , [51] , [52] , [53] , [54] , [55] , [56] , [57] , [58] , [59] , [60] , [61] , [62] were included in our meta-analysis. The mean age of operative patients with COVID-19 was 50.91 [95% CI, 42.49; 59.34], and 49% [95% CI, 0.33, 0.65] patients were female.…”
Section: Resultsmentioning
confidence: 99%
“…The characteristics of included trials were presented in Table 1 . A total of 269 patients from 47 studies [16] , [17] , [18] , [19] , [20] , [21] , [22] , [23] , [24] , [25] , [26] , [27] , [28] , [29] , [30] , [31] , [32] , [33] , [34] , [35] , [36] , [37] , [38] , [39] , [40] , [41] , [42] , [43] , [44] , [45] , [46] , [47] , [48] , [49] , [50] , [51] , [52] , [53] , [54] , [55] , [56] , [57] , [58] , [59] , [60] , [61] , [62] were included in our meta-analysis. The mean age of operative patients with COVID-19 was 50.91 [95% CI, 42.49; 59.34], and 49% [95% CI, 0.33, 0.65] patients were female.…”
Section: Resultsmentioning
confidence: 99%
“…We strongly believe that it is not the right way and we decided to preserve our activity. One must take into account that COVID-19 targets lungs, resulting in a restrictive alteration both in early and middle phases; the first transplants for this disease have already been carried out in China [ 10 ]. Health authorities should seek proper balance between the massive commitment to the pandemic and the identification of pathways reserved for the treatment of the most critical patients in need of a transplant.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, increasing the pH value in vesicles loaded with viruses can be an important mechanism of Metformin against SARS-CoV-2 [8]. Furthermore, Metformin can reverse established lung fibrosis, so it has been suggested that Metformin may be an effective treatment of COVID-19-related pulmonary fibrosis [9,10]. Taken together, all these data support the opinion that Metformin can be a beneficial adjuvant therapy for patients in acute, chronic, and even recovery phases of COVID-19.…”
Section: To the Editormentioning
confidence: 99%